Board independence, sub-committee independence and firm performance: evidence from Australia - Singhchawla, W.; Evans, Robert; Evans, John (Curtin University of Technology. School of Economics and Finance, 2011)
This study investigates whether the monitoring of company management by an independent board of directors serves to enhance firm performance in Australia. The paper explores in detail the impact of the level of independence of the main board and sub-committees including audit, remuneration and nomination on performance in a sample of 250 listed companies. From the perspective of a regulator, the study’s findings have implications and suggest that an independent main board produces superior results. The shareholding of independent directors is also found to negatively impact performance for this data, suggesting that their role as independent arbiter is restricted by shareholding. Interestingly, the returns to firm performance engendered by independence did not extend to the composition of sub-committees, where the presence of outside directors did not significantly influence performance.